Pengaruh Variasi Pupuk terhadap Pertumbuhan Benih Terung Hijau (Solanum melongena L.) - Putri, Yuni Suwarni; Utami, Septiana Dwi; Fitriani, Herdiyana (Biocaster : Jurnal Kajian Biologi, 2022)
Eggplant (Solanum melongena L.) is a garden plant grown for its fruit. Some green eggplant farmers in West Lombok, use NPK fertilizer as the main choice to produce quality fruit, they never use organic fertilizer when planting green eggplant for fear that the size of the fruit produced is not as big as the fruit grown using NPK. Low quality green eggplants are rarely in demand by the public, so it will have an impact on decreasing selling prices in the market. This study aims to determine the effect of fertilizer variation on the growth of green eggplant (Solanum melongena L). This research is a true experiment that wants to see the growth of green eggplant plants given a variety of fertilizers. In this study using 3 treatments, namely PA (chicken manure + soil in a ratio of 2:1), PK (goat manure + soil in a ratio of 2:1), PN (NPK fertilizer 20 g given to each polybag size 2 kg). The results of the analysis from the table and the average diagram, the application of fertilizer variations showed that there were differences in the growth of green eggplant plants on the parameters of plant height, number of leaves, number of branches, number of flowers and number of fruit. The results of the ANOVA statistical test showed that there was an effect of fertilizer variation on the parameters of the number of leaves and the number of branches, but it was not significant on the parameters of plant height, number of flowers and number of green eggplant (Solanum melongena L.).